Pembelajaran Sosial Emosional: Konsep, Permasalahan, Solusi dan Gagasan Pengembangan di Sekolah Dasar - Khairunnisya Khairunnisya (Jurnal Pendidikan Tuntas, 2025)
Social emotional learning (SEL) is an educational approach that focuses on developing social and emotional skills, attitudes and values in learners. This literature review aims to understand the basic concept of SEL, identify problems in its implementation, and offer solutions and development ideas in the primary school environment. The method used is content analysis and narrative synthesis of relevant literature, focusing on publications from 2003 to 2025. The results show that SEL plays an important role in improving learners' motivation to learn, academic outcomes, and social skills. However, the implementation of SEL still faces challenges such as lack of teacher training, lack of integration in the curriculum, and low student motivation due to lack of understanding and practice of SEL in the classroom. Proposed solutions include teacher training, integration of SEL in learning, and development of collaborative and project-based learning models. The article also provides ideas for the development of SEL through literacy approaches, emotional education, and the creation of a safe and inclusive learning environment.